Disclosures About Key Value Drivers in M&A Announcement Press Releases: An Exploratory Study. (21st July 2021) - Filip, Andrei; Lobo, Gerald J.; Paugam, Luc; Stolowy, Hervé
Abstract : We investigate the association between disclosures about key value drivers (i.e., growth, synergies, human capital, brands, customers, and technology) in press releases announcing mergers and acquisitions (M&A) deals and acquirer stock returns upon the announcement. We find that, after controlling for the main characteristics of the deal, acquirers that use more terms about these value drivers in press releases exhibit more negative market returns around the M&A announcement. An increase of 10% in the number of terms used about generic value drivers is associated with a decrease in announcement market‐adjusted returns of approximately 43 basis points. The negative association between terms about value drivers and acquirer stock returns is stronger for larger deals. We also find that disclosures about these value drivers in M&A announcement press releases are consistent with the subsequent subjective valuation of intangible assets recognized in acquirers' financial statements through the purchase price allocation. Our findings are relevant for investors attempting to interpret early signals about the performance of M&A and for managers communicating about these strategic investment decisions.